Preformulation of Lemongrass Oil (Cymbopogon citrates (DC) Stapf) and Turmeric Extract (Curcuma xanthorrhiza Roxb.) on the Growth of Escherichia coli Bacteria - Werti; Vriezka Mierza; Sumardi (Yayasan Penelitian dan Inovasi Sumatera, 2023)
Background: Lemongrass and turmeric are medicinal plants known for their antibacterial properties due to the presence of compounds such as alkaloids and flavonoids in lemongrass oil, and saponins and flavonoids in turmeric. Typically, lemongrass oil is used for massage oil, and turmeric is commonly used as a spice and traditional medicine. However, there is limited scientific information on the combination of both. Objective: This study aims to evaluate the antibacterial potential of a formulation combining lemongrass oil and turmeric extract against Escherichia coli bacteria, both in extract form. Method: The research steps include the preparation of the plant materials, extraction, granulation process, and antibacterial testing. Extraction is performed using boiling with distilled water as the solvent. The antibacterial activity testing method employed is the good diffusion method. Results: The formulation of lemongrass oil (Cymbopogon citratus (DC) Stapf) and turmeric (Curcuma xanthorrhiza Roxb.) has demonstrated antibacterial activity against Escherichia coli in both extract and granule forms across five different formulations. Conclusion: The highest inhibition diameter was observed with the combination of lemongrass oil and turmeric extract at 19.05 mm, and lemongrass oil and turmeric granules at 18.71 mm, in Formula 3 (0.25 lemongrass oil: 0.75 turmeric).